2022
DOI: 10.4081/ija.2021.1976
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of some agronomic traits in a collection of wheat (<em>Triticum turgidum</em> L. sp.pl.) genotypes under South Mediterranean growth conditions

Abstract: Genetic variability of some agronomic traits were investigated in 60 tetraploid wheat accessions (Triticum turgidum L. ssp) under rainfed conditions. The results indicated the presence of sufficient variability for all measured traits.The highest phenotypic and genotypic coefficient of variation was recorded for yield and awn length. High heritability coupled with high genetic advance and high expected response to selection recorded for thousand-grain weight, awn length, and the number of grains per spike. Clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Wu et al (2018a) conducted a genetic diversity analysis on seven agronomic traits, including PH, FW, and DW, and the results showed that the CV of each trait was >10%. The CV of each trait in this study was high (>5%, RSL CV <5% only for 2019-2020, Tables 3-5), which could be regarded as producing large variation (Bendjama and Ramdani, 2022), indicating that the agronomic traits in this study are rich in genetic diversity. The richer the genetic diversity of a species, the greater its ability to adapt to its environment and its evolutionary potential (Nevo et al, 2012).…”
Section: Figurementioning
confidence: 67%
“…Wu et al (2018a) conducted a genetic diversity analysis on seven agronomic traits, including PH, FW, and DW, and the results showed that the CV of each trait was >10%. The CV of each trait in this study was high (>5%, RSL CV <5% only for 2019-2020, Tables 3-5), which could be regarded as producing large variation (Bendjama and Ramdani, 2022), indicating that the agronomic traits in this study are rich in genetic diversity. The richer the genetic diversity of a species, the greater its ability to adapt to its environment and its evolutionary potential (Nevo et al, 2012).…”
Section: Figurementioning
confidence: 67%
“…Bendjama and Ramdani (2022) [20] also observed high heritability for most agromorphological traits in local durum wheat varieties grown in Algeria. However, broadsense heritability varies depending on the population and environmental conditions [41], and it does not reveal the specific genetic mechanisms underlying the traits [19].…”
Section: Discussionmentioning
confidence: 89%
“…Genetic and non-genetic parameters, such as phenotypic (CV p ) and genotypic coefficient of variation (CV g ), along with heritability (h 2 bs ), serve as valuable biometric indicators for assessing the genetic variation and adaptability within a germplasm collection. They provide insights into the relative contributions of genetic and environmental factors to observed variations in specific traits among individuals [19][20][21].…”
Section: Introductionmentioning
confidence: 99%